(untitled) (The International Journal for Scientific Research, 2025)
This research examines the legal and jurisprudential characterization of cases where financial brokers are not obligated to provide compensation in the Saudi market. It aims to study situations where the financial broker’s liability for compensation is negated and establish this from both legal and jurisprudential perspectives. The research’s significance lies in clarifying the controls and standards that govern financial brokers’ responsibility and determining cases where compensation is not required. The research adopted descriptive-analytical and comparative approaches, analyzing legal and jurisprudential texts related to the subject and comparing legal and jurisprudential characterizations. The study included an analysis of judicial applications from 2003 to 2024, focusing on decisions by the Committees for Resolution of Securities Disputes. The research scope was limited to studying the Saudi financial market, with emphasis on cases where financial brokers’ compensation liability is negated. The research concluded that there are specific cases where the financial broker’s liability for compensation is negated, including force majeure, technical errors in the trading system, execution of client orders according to established procedures, and the absence of a causal relationship between error and damage. The study also demonstrated the importance of integration between the Saudi system and Islamic jurisprudence in regulating financial brokerage provisions. Based on these findings, the research recommends developing the regulatory framework for financial brokerage and updating electronic monitoring mechanisms for trading. It also emphasizes the importance of enhancing professional training programs for brokers and developing a unified system for documenting and preserving client orders. These recommendations aim to improve financial market efficiency and protect the rights of all market participants.